Organizzazione produttiva e politiche per la conciliazione in un’azienda del Mezzogiorno d’Italia - Sacco, Enrico (Cambio. Rivista sulle Trasformazioni Sociali, 2018)
The objective of the present analysis is to understand some of the social and institutional dynamics on which gender asymmetry is founded within large companies. The idea was to study, in a region of Southern Italy, a productive organization in the service sector that has recently adopted policies and strategies for the conciliation. The basic hypothesis that has oriented the case study is that the results of these interventions depend on social and cultural factors and specific managerial cultures. More specifically, we focus on: (1) the organization of work activities and its influence on private and family lives; (2) the main difficulties related to the employment conditions and their consequences on future prospects; (3) the ability – and the inability – of the trade unions to comprehend the needs of women workers and (4) the impact of top management decisions in the field of conciliation policies.